Uloga i značaj studije za maloljetnike u postupku izvršenja krivičnih sankcija prema maloljetnicima u Bosni i Hercegovini / The Role and Significance of Juvenile Judges in the Process of Execution of Criminal Sanctions for Jeveniles in Bosnia and Herzegovina - Pleh, Vildana (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
In performing its function of adjudication, the court is one of the most important entities in criminal law. With its meritorious decisions, as well as decisions of other legal nature, juvenile judges direct, guide, and finalise the processes involving juvenile perpetrators, trying to come up with the best ways how to achieve what is in the best interest of a minor, individualising the available instruments for tackling juvenile delinquency both in the stage of pronouncement and enforcement or execution of sanctions. In addition to general discussions on various forms of state intervention concerning delinquent behaviour of juveniles, the author of the paper focuses precisely on the role, position, and the significance of juvenile judges in Bosnia and Herzegovina’s juvenile criminal legislation. Acknowledging the role and significance of all juvenile justice entities, the court stands out as a particular authority and its role is analysed through four key roles of the court in the process of enforcement and execution of criminal sanctions, including both alternative sanctions and criminal sanctions of institutional treatment. The author has generally reflected in that sense on the aforementioned roles of the court, highlighting the condition in legislation and practice in Bosnia and Herzegovina, meaning at the level of Municipal Court of Sarajevo.